Lichhavikalin Basti Hamsaghrihadranga ra Thyanka Prasiddha Baishnav Devata Lokpal Swami : Khojmulak Tippani - Chalise, Pushpa Raj (Tribhuvan University Journal, 2011)
Available with Full text. Key words: Lichhavikalin; Baishnav Devata; Lokpal Swami Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 119-127 Uploaded date: 21 April, 2011